Can Mathematics and Statistics Perception Explain Students' Statistical Literacy? - Auliya, Risma Nurul (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2018)
The aim of this research is intended to examine the effect of mathematics and statistics perception towards studentsâ€™ statistical literacy. The research utilized a survey method with quantitative approach. The research population was undergraduate students from major informatics in one of university in Jakarta. The sample consisted of 80 students, 50 of students were male, while 30 of the students were female. All the participants belonged to similar grade level and enrolled in a statistics course. A survey instrument entitled â€œMathematics and Statistics Perception Scale (MSPS)â€ was intended to examine undergraduate studentsâ€™ perceptions of self-efficacy and their attitudes toward the application of statistics in real world settings. The initial scale consisted of 15 items and the final version consists of 11 items. A multiple-choice survey with 22 questions measuring statistical literacy skills and consisted of items measuring skills on interpreting or critiquing the prevalence of statistical phrases and ideas in the media. The data collected were analyzed using linear regression. The result of the analyses showed mathematics and statistics perception has an influence in the way studentsâ€™ statistical literacy skills.